Kerangka Kerja Asesmen dan Intervensi Bahasa Lisan Usia Prasekolah di Indonesia: Studi Pendahuluan - Rexsy Taruna (Jurnal Terapi Wicara, 2023)
This study aims to provide preliminary evidence regarding the important role of prelinguistic abilities in language development. This study involved 29 preschool children. Each child is assessed individually using the developmental profile and assessment of social and communication skills. After all the data is obtained, the data on each variable will be converted into a z-score before statistical analysis is carried out. Based on the correlation analysis, it is known that there is a correlation between joint attention and language (r = 0.697; p <.001), symbolic play and language (r = 0.820; p <.001), imitation and language (r = 0.680). ;p <.001), and gesture with language (r = 0.697; p <.001). This study provides preliminary evidence that it is important to consider prelinguistic abilities in language skills assessment and intervention.